The book of magic - Hoffman, Alice (Simon & Schuster, 2021)
"The Owens family has been cursed in matters of love for over three-hundred years but all of that is about to change. The novel begins in a library, the best place for a story to be conjured, when beloved aunt Jet Owens hears the deathwatch beetle and knows she has only seven days to live. Jet is not the only one in danger--the curse is already at work"--